On the identity of Crotalaria nallamalayana Rasingam & J. Swamy (Fabaceae) - Arigela, Ravi Kiran; Singh, Rajeev Kumar (Phytotaxa, 2018)
The monotypic genus Pycnospora R. Br. ex Wight &Arn. (1834: 197) with recognised species Pycnospora lutescens (Poir.) Schindl. (1926: 145) of family Fabaceae: Faboideae is distributed in Old World tropics (Mabberley 2017). During the taxonomic study of Pycnospora, authors noticed that the recently published new species Crotalaria nallamalayana Rasingam & J. Swamy by Rasingam et al. (2018: 159) in family Fabaceae from Amrabad Tiger Reserve, Mahabubnagar district, Telangana, India is not new to science, but it is well known species of the family Fabaceae (subfamily Faboideae) in the name Pycnospora lutescens. The description, colour images and characters given for stems, leaves and leaflets, petioles, petiolules, inflorescences, peduncles, bracts, flowers, calyx, corolla, stamens, gynoecium, pods and seeds in the protologue of Crotalaria nallamalayana is perfectly matching with the typical Pycnospora lutescens (Poir.) Schindl. Therefore, the species Crotalaria nallamalayana Rasingam & J. Swamy is treated here as a new synonym of Pycnospora lutescens.